AN INTELLIGENT MAXIMUM POWER POINT SOLAR TRACKING SYSTEM - Mirza, Nada Masood (Journal of Applied Engineering Science, 2019)
This paper accentuates the enhancement of electric energy produced from Photo Voltaic (PV) solar modules as a result of sun tracking. The development of the tracking system is based on finding the orientation of a solar module at which maximum power is delivered. Two approaches for monitoring “Real-time power” have been demonstrated namely Pulse Width Modulation (PWM) based circuit and varying resistive load using analog switches. The approaches are meant to obtain Voltage-Current   (VI)   curve of the solar panel and consequently locate the Maximum Power   Point (MPP).  A  modified  form  of  the  Perturb  &  Observe (P&O) algorithm  has  been  used  for tracking. The tracking system has many advantages  in  relation  to similar devices. It is intelligent in a way that it not only performs real-time power monitoring but also has  the  ability  to store   information   and   improve   behavior   based   on previous   tracking   history.   The   effectiveness   of   the proposed   tracking   scheme   has   been    demonstrated experimentally on a commercially available single axis solar tracking platform
Keywords: Solar Tracking System; Single Axis Tracker; PV; MPP